(untitled) (Scientific journal of the Fergana State University, 2026)
This article investigates how AI-powered mobile applications such as ELSA Speak and Speechace can support the development of speaking skills among EFL learners. By employing Audio-Articulatory and Pronunciation-Based Approaches, these tools offer real-time, personalized feedback on pronunciation, fluency, and stress patterns. The study emphasizes the effectiveness of integrating multiple AI platforms into the learning process to meet diverse learner needs and improve communicative competence.